Observations on “the equal” and “the equals”: Phaedo 72e”‘77a: Fédon 72e-77a - Santos, José Gabriel (Revista Archai, 2016)
Though Platonic anamnesis relates two different acts of knowledge ”“ one grasped through sense perception, the other conceived in the mind ”“, from an ontoepistemological point of view, I propose to see them as one single cognitive act, described from different perspectives. Though this intellectual ‘conception’ of knowledge occurs only after “something” has been grasped from sense perceptions (74c, 75a, b, e, 75e”‘76a), what is known (73c, d) through the senses (74d) refers and is compared to entities previously conceived in the mind (75b,76d”‘e). As a theory of cognition and learning, anamnesis consists in the reciprocal remission of these two acts of knowledge: one ‘grasped’ from the perception of something; the other conceived as a cognitive content kept in the soul, subsequently recovered through the experience of sense perceptions (76d”‘e; Men. 82”‘86; Phdr. 249b”‘c). In the given example, such interpretation is possible if what is grasped does not correspond to any predicates attributed to equal or unequal sticks and stones, but to “the very equals” (74b), understood as perceptual images of the equal: “the model they are formed from”, to which they refer. As a cognitive conception and a theory of the acquisition of knowledge, anamnesis consists in the gradual process started “by the use of sense perceptions” through which the soul recovers the knowledge which is its own (75e; Phd. 249b ss.).